2022
DOI: 10.1051/0004-6361/202142076
|View full text |Cite
|
Sign up to set email alerts
|

Type II supernovae from the Carnegie Supernova Project-I

Abstract: Linking supernovae to their progenitors is a powerful method for furthering our understanding of the physical origin of their observed differences while at the same time testing stellar evolution theory. In this second study of a series of three papers where we characterise type II supernovae (SNe II) to understand their diversity, we derive progenitor properties (initial and ejecta masses and radius), explosion energy, and 56Ni mass and its degree of mixing within the ejecta for a large sample of SNe II. This… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 164 publications
1
24
0
2
Order By: Relevance
“…Morozova et al 2018;Förster et al 2018;Eldridge et al 2019;Ricks & Dwarkadas 2019;Martinez & Bersten 2019;Martinez et al 2020;Utrobin et al 2021). Recently, Martinez et al (2022) presented results from hydrodynamical modelling to 53 SNe II, finding a maximum initial mass of 21.3 M ⊙ . A third alternative method to infer Mi is by comparing late-time spectra with nebular spectra models (e.g.…”
Section: ; O'mentioning
confidence: 99%
See 4 more Smart Citations
“…Morozova et al 2018;Förster et al 2018;Eldridge et al 2019;Ricks & Dwarkadas 2019;Martinez & Bersten 2019;Martinez et al 2020;Utrobin et al 2021). Recently, Martinez et al (2022) presented results from hydrodynamical modelling to 53 SNe II, finding a maximum initial mass of 21.3 M ⊙ . A third alternative method to infer Mi is by comparing late-time spectra with nebular spectra models (e.g.…”
Section: ; O'mentioning
confidence: 99%
“…This relation depends on the stellar evolution model adopted in each work. Morozova et al (2018) and Martinez et al (2020Martinez et al ( , 2022) reported Mi values inferred by fitting hydrodynamical models to SN data. Morozova et al (2018) used multiband light-curve models generated with the SNEC code (Morozova et al 2015), while Martinez et al (2020Martinez et al ( , 2022 used bolometric light curves and expansion velocity curves calculated with the model of Bersten et al (2011).…”
Section: Comparison With Initial Masses From Modelsmentioning
confidence: 99%
See 3 more Smart Citations